Encyclopedia of Life Sciences 2016
DOI: 10.1002/9780470015902.a0001920.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Cutin and Suberin Polyesters

Abstract: Cutin and suberin are cell wall‐associated glycerolipid polymers that are specific to plants. Cutin forms the framework of the cuticle sealing the aerial epidermis, while suberin is present in the periderm of barks and underground organs. Suberised walls are also found in the root endodermis. Barriers based on cutin and suberin restrict the transport of water and solutes across cell walls and limit pathogen invasions. Chemical analysis shows that both polymers are polyesters composed mostly of fatty hydroxyaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…When suberin is depolymerized, the main components are long-chain aliphatic acids, typically 80%–90% of depolymerisates [19]. Suberin fatty acids are covalently linked through esterification to ferulic acid and neighboring lignin-like polyaromatics [12,19,20,21]. Suberin is believed to form partly orderly lamellar structures [19,22].…”
Section: Introductionmentioning
confidence: 99%
“…When suberin is depolymerized, the main components are long-chain aliphatic acids, typically 80%–90% of depolymerisates [19]. Suberin fatty acids are covalently linked through esterification to ferulic acid and neighboring lignin-like polyaromatics [12,19,20,21]. Suberin is believed to form partly orderly lamellar structures [19,22].…”
Section: Introductionmentioning
confidence: 99%
“…Distinctly, polyphenols and lipids related metabolites were significantly enriched in Z0284, which may play a basal role prior to exposure to low-N stress. It has been widely reported that biotic and abiotic factors can induce polyphenol accumulation in plants Similarly, cellular lipid levels (mainly glycerolipids) also play essential roles in response to environmental stress [38,39]. In algae, nitrogen depletion has been defined as one of the best lipid accumulator stress condition [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Plants secrete hydrophobic compounds into the apoplast, where they contribute substantially to the plant’s structural strength and resistance against environmental stresses ( Kumar et al, 2016 ; Li-Beisson et al, 2016 ; Figure 1 ). Both lignin and suberin depositions are modifications of the secondary cell walls of land plants ( Kumar et al, 2016 ; Figure 1 ), corroborating their function in rigidifying tissues predominated by dead cells (xylem, periderm; Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“… Overview of the localizations of lignin, suberin, cutin, and cutan; their major precursors; and hypothetical polymer structures. Major organ- and tissue-specific localizations of the four hydrophobic biopolymers are as follows: lignin in vascular bundles of shoots and roots, in structural tissues, such as leaf sclerenchyma, and in idioblasts, such as fruit stone cells ( Kumar et al, 2016 ); suberin in stem periderm and root endodermis (Casparian strip; Franke and Schreiber, 2007 ); cutin in the epidermal cuticle of leaves ( Bourgault et al, 2020 ) and flowers (“nanobridges”; Li-Beisson et al, 2016 ) and in the root cap ( Berhin et al, 2019 ); and cutan in the leaf and fruit cuticle of some species, such as Vaccinium myrtillus ( Boom et al, 2005 ; Kallio et al, 2006 ). Examples of common constituents of the four biopolymers are as follows: lignin: three monolignols (H, G, and S), ferulate monolignol ester (similar to coumarate ester, not shown), and tricin represent lignin building blocks.…”
Section: Introductionmentioning
confidence: 99%